GeSn/GaAs hetero-structure by magnetron sputtering - Qian, Li (2021)
We report high quality GeSn/GaAs heterostructure photodetectors grown by a modified magnetron sputtering system. A metal-semiconductor-metal photoconductor is fabricated to examine the ability of photodetection for GeSn alloy. Then the GeSn/GaAs heterostructure photodetector is first demonstrated with a detectivity of.8× 10^{9}$ Jones achieved at 1450 nm under an applied reverse voltage bias of -0.1 V, which is comparable to or even better than the GeSn-based photodetectors grown by chemical vapor deposition. The work provides an alternative technique for low cost and large-area fabrication of GeSn based devices.